Public Investment Scaling-up and Debt Sustainability : The Case of Energy Sector Investments in the Caribbean - El-Ashram, Ahmed (Washington, D.C. : International Monetary Fund, 2017)
The question of how scaling up public investment could affect fiscal and debt sustainability is key for countries needing to fill infrastructure gaps and build resilience. This paper proposes a bottom-up approach to assess large public investments that are potentially self-financing and reflect their impact in macro-fiscal projections that underpin the IMF's Debt Sustainability Analysis Framework. Using the case of energy sector investments in Caribbean countries, the paper shows how to avoid biases against good projects that pay off over long horizons and ensure that transformative investments are not sacrificed to myopic assessments of debt sustainability risks. The approach is applicable to any macro-critical investment for which user fees can cover financing costs and which has the potential to raise growth without crowding-out.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet